Fashion Sebagai Strategi Simbolik Komunikasi Non-Verbal - Dion Dewa Barata (Universitas Multimedia Nusantara, 2010)
Fashion it is not just how to dress, branding, or designing clothes, especially in the contemporary society. Fasyen has become a medium of communication in which identity is represented. This study tried to see fasyen through cultural studies perspective to look at its role in the search for identity. Using a semiotic approach can be seen that fasyen are constraceted by series of signs that systemically designed to serve a particular ideology. As part of our daily life, fashion also used as a means to enter in a particular social group which then will affect their daily behavior Keywords: Fashion, Cultural Studies, Semiotic, Identity, Representation